A heuristic study of UK nurses' migration to WA: Living the dream downunder. Issue 1 (February 2018) - Vafeas, Caroline; Hendricks, Joyce
Abstract: Background: Demands on the health care system, a growing ageing population and the age profile within the current nursing workforce have placed Australia in a position to expect a future shortage of nurses. One solution to this shortage could be to attract overseas trained nurses, who may provide a readymade and experienced addition to the workforce. Aim: This study aimed to investigate similarities found in the individual and unique migration journeys of 21 registered nurses. Each of the nurses in this study migrated from the United Kingdom to Perth in Western Australia. Methods: The research methodology chosen was Heuristic inquiry. Participants were recruited using purposive sampling, and snowballing was utilised to provide ease of access to eligible participants. Data was collected through a focus group, individual semi-structured interviews, and a journal. Findings: In this study, three main coping strategies were identified: (a) developing resilience; (b) finding a new professional identity; and (c) having the ability to adapt to a new life. It was found that feelings of belonging were necessary to make the move a success. Participants placed the need to develop new friendships and a replacement family as a high priority. Discussion: Migration offers a unique experience. Success during the complex migration process depended on the migrant RNs' ability to adapt to a new country and to develop strategies that assist in dealing with the new and unfamiliar. Conclusion: This study highlighted many of the issues that need to be considered by future nurses migrating to Western Australia from United Kingdom. Learning from the experiences of past migrants can assist future nurses to "live the dream" that Australia offers, both professionally and personally.